2020
DOI: 10.1161/circep.120.008461
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Left Ventricular Function and Heart Failure Symptoms on Outcomes Post Ablation of Atrial Fibrillation in Heart Failure

Abstract: Background - Recent data demonstrates promising effects on left ventricular (LV) dysfunction and LV ejection fraction (EF) improvement following ablation for atrial fibrillation (AF) in patients with heart failure (HF). We sought to study the relationship between LVEF, NYHA class on presentation and the endpoints of mortality and HF admissions in the CASTLE-AF study population. Furthermore, predictors for LVEF improvement were examined. Methods - The CA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
45
1
10

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 66 publications
(56 citation statements)
references
References 39 publications
0
45
1
10
Order By: Relevance
“…The mechanisms initiating and perpetuating AF are still not completely understood and therefore, ablation strategies are heterogeneous. Several observations have led to individual mechanistic insights in AF management and arrhythmiaassociated cardiac remodeling which emphasize the need for personalized paths in AF therapy [2,3]. Despite improvements in ablation technology, imaging modalities, and ablation techniques, the recurrence of atrial arrhythmias after AF ablation still remains frequent [1,4].…”
Section: Introductionmentioning
confidence: 99%
“…The mechanisms initiating and perpetuating AF are still not completely understood and therefore, ablation strategies are heterogeneous. Several observations have led to individual mechanistic insights in AF management and arrhythmiaassociated cardiac remodeling which emphasize the need for personalized paths in AF therapy [2,3]. Despite improvements in ablation technology, imaging modalities, and ablation techniques, the recurrence of atrial arrhythmias after AF ablation still remains frequent [1,4].…”
Section: Introductionmentioning
confidence: 99%
“…These observations led to the suggestion that there might be a substantial degree of AF‐induced structural LV remodelling in HF patients and even in those without LV dysfunction. In this context, recent data demonstrated that sinus rhythm after successful AF ablation resulted in reverse LV remodelling and improvement of the LV function as well as HF symptoms 1,20–22 . Irrespective of these findings, open questions remain regarding selection of adequate patients and validity of the findings in patients with terminal HF and severely impaired LV function.…”
Section: Discussionmentioning
confidence: 99%
“…In this context, recent data demonstrated that sinus rhythm after successful AF ablation resulted in reverse LV remodelling and improvement of the LV function as well as HF symptoms. 1, [20][21][22] Irrespective of these findings, open questions remain regarding selection of adequate patients and validity of the findings in patients with terminal HF and severely impaired LV function. As mentioned earlier, patients with end-stage HF eligible or listed for HTx represent a separate and highly specialized cohort, as these patients have been excluded from all major and guideline relevant clinical trials.…”
Section: Discussionmentioning
confidence: 99%
“…Patients with more advanced HF, lower LVEF, and larger atrial size may benefit less from catheter ablation. 64 The role of the hybrid convergent procedure compared to standard catheter ablation in patients with AF and HF also will need to be studied.…”
Section: Future Directionsmentioning
confidence: 99%